Pseudoprogression in CAR-T cell therapy for solid tumor: Case report - Xuan Zhao; Xuan Zhao; Yanfen Liu; Yanfen Liu; Guohui Qin; Guohui Qin; Yan Ge; Qinglong Li; Xinfeng Chen; Xinfeng Chen; Ximei Tian; Yong Yu; et al. (Frontiers in Immunology)
We reported the pseudoprogression in an elderly patient with advanced gastric cancer after chimeric antigen receptor (CAR)-T cell therapy. The hepatic metastases enlarged 1 month after CAR-T cell infusion and then shrunk the next month as seen through computed tomography scanning. Based on a comprehensive evaluation that includes imaging, pathology, serum tumor markers, and clinical symptoms, we arrived at a diagnosis of pseudoprogression after CAR-T cell therapy, which has not been reported in previous studies. In this report, we provide detailed descriptions of the patient’s clinical presentation, imaging findings, treatment process, and follow-up outcomes. We believe that this case holds important implications for CAR-T cell therapy research and offers valuable insights for clinical practice.